Wnt signaling regulates hepatobiliary repair following cholestatic liver injury in mice - Okabe, Hirohisa; Yang, Jing; Sylakowski, Kyle; Yovchev, Mladen; Miyagawa, Yoshitaka; Nagarajan, Shanmugam; Chikina, Maria; Thompson, Michael; Oertel, Michael; Baba, Hideo; Monga, Satdarshan P; Nejak‐Bowen, Kari Nichole (Hepatology (Baltimore, Md.), 2016)
Hepatic repair is directed chiefly by the proliferation of resident mature epithelial cells. Furthermore, if predominant injury is to cholangiocytes, the hepatocytes can transdifferentiate to cholangiocytes to assist in the repair and vice versa, as shown by various fate‐tracing studies. However, the molecular bases of reprogramming remain elusive. Using two models of biliary injury where repair occurs through cholangiocyte proliferation and hepatocyte transdifferentiation to cholangiocytes, we identify an important role of Wnt signaling. First we identify up‐regulation of specific Wnt proteins in the cholangiocytes. Next, using conditional knockouts of Wntless and Wnt coreceptors low‐density lipoprotein‐related protein 5/6, transgenic mice expressing stable β‐catenin, and in vitro studies, we show a role of Wnt signaling through β‐catenin in hepatocyte to biliary transdifferentiation. Last, we show that specific Wnts regulate cholangiocyte proliferation, but in a β‐catenin‐independent manner. Conclusion: Wnt signaling regulates hepatobiliary repair after cholestatic injury in both β‐catenin‐dependent and ‐independent manners. (Hepatology 2016;64:1652‐1666)